230k views
0 votes
(8 - (-1)Step 2 of 4: Find (g - (-1)Enable Zoom/Pan8(x) = -x-210-5-5f(x) = 2x + 1

(8 - (-1)Step 2 of 4: Find (g - (-1)Enable Zoom/Pan8(x) = -x-210-5-5f(x) = 2x + 1-example-1
User DenisGL
by
3.6k points

1 Answer

4 votes

Answer:


(g-f)(-1)\text{ = 0}

Step-by-step explanation:

Here, we want to calculate (g-f)(-1)

We start by subtracting f(x) from g(x)

Then we proceed to substitute -1 for x

Mathematically, we have that as:


\begin{gathered} -x-2\text{ -\lparen2x+1\rparen} \\ -x-2-2x-1\text{ = -x-2x-2-1 = -3x-3} \end{gathered}

Now, we substitute -1 for x as follows:


\begin{gathered} -3(-1)\text{ - 3} \\ =\text{ 3-3 = 0} \end{gathered}

User Ithar
by
4.3k points